Analysing the Sakuga technique in the animation of Mob Psycho 100 (2016) / Muhammad Hazim Hazmi @ Azmi and Siti Nur Ain Abd Rahman - Hazmi @ Azmi, Muhammad Hazim; Abd Rahman, Siti Nur Ain (Faculty of Art and Design, 2024)
What aspects of an action scenario make it effective? That question has been on the minds of filmmakers, animators, audiences, and fans for a while, and there are as many responses as possible to it. However, there might be a few general characteristics that, when applied in one way or another, give a scene its personality and, perhaps, make it enjoyable for the viewer thanks to the Sakuga technique. In this paper, the researcher will discuss the topic of Sakuga, one of the branches of the animation method by analysing the Sakuga technique in the animation Mob Psycho 100 released in 2016. The researcher will also cover the background research on the term Sakuga used in this study. Sakuga is a type of animation that is mostly used in the Japanese anime series Mob Psycho 100. The researcher will discuss the relevant use of this animation technique and how it influences or has an impact on other animation subcultures when using this method, in addition to the study problem statement and the research objective, both of which are presented in this paper. A topic that is relevant to the research investigations and its constraints will be decided together with the objective and its challenges. The study's importance, scope, and limits will all be addressed along with the Animetism Theory from the book The Anime Machine as the theoretical framework.